Assessing Urban Carbon Sequestration Capacity under Land Use Changes - Tawakkal, Irfan; Anggraini, Nani; Muis, Ramdiana; Fariz, Reza Darma Al; Akrim, Djusdil; Hutagalung, Ira Rumiris; Rachman, Indriyani; Matsumoto, Toru (Universitas Diponegoro, 2025)
A significant amount of global greenhouse gas (GHG) emissions comes from Indonesia, largely driven by deforestation and land degradation. As a developing nation, it is also dealing with the growing pressures of urban expansion. This study assesses the distribution of carbon stock in Parepare City, South Sulawesi, Indonesia. Notably, Parepare City has not yet experienced extensive land-use transformations, retaining substantial carbon stock, which positions it as a proactive case study for preventing future carbon loss amidst ongoing urbanization. Using the InVEST Carbon Storage and Sequestration model with SPOT 7 satellite imagery (2016) and global carbon density data, the research quantifies carbon storage across various land use/land cover (LULC) types. Analysis reveals natural ecosystems, particularly mixed forests and fields, hold the highest carbon storage potential. The total estimated carbon stock in Parepare City is 1,456,909.41 Mg C. These findings emphasize the urgent need for climate-responsive land management, including forest conservation, and urban greening, to enhance local carbon sinks and support Indonesia's climate change mitigation goals. This assessment provides crucial insights for urban planners and policymakers to balance growth with ecosystem conservation for a susta00inable future.